Analysis of Automotive Suspension System Failures and Reliability Evaluation: A Study Based on V-SIM Simulation - Sławomir Kowalski (Applied Sciences)
This article presents the factors that are conducive to the faster degradation of suspension system components with examples of typical system damage seen at diagnostic stations. Further in the article, the simulation of the deflection of the suspension system was conducted in the V-SIM 5.0 software, and the sample road consequences of damage to the system were presented. The simulation results showed that long-term use of the vehicle on uneven roads often leads to maximum deviations of the suspension system, even 150 mm. The consequence of such a condition may be its damage during driving, resulting in a road accident. The effects of damage to the suspension system were simulated while driving at a speed of 50 and 70 km/h. The article concludes with an estimation of the reliability indicators of the suspension system. Based on the results, it may be concluded that the operation of a fully loaded car in difficult conditions causes a 50% decrease in the system’s reliability as early as at a mileage of approximately 48,000 km.